(untitled) (Psychology Travelogs, 2024)
The article is devoted to the problem of interpersonal relationships of adolescents. The purpose of the article is to present the results of an empirical study of the relationship between interpersonal relationships and emotional intelligence in adolescents. The following psychodiagnostic tools were used for the empirical study: T. Leary’s method “Diagnostics of Interpersonal Relationships”; V. Stefanson’s method of studying interpersonal relationships “Q-sorting”; Schutte’s emotional intelligence test; N. Epstein and A. Mehrabian’s method “Diagnostics of Empathy”. The study was conducted on the basis of the State Vocational and Technical Educational Institution “Krasylivkyi Professional Lyceum”. 36 adolescents aged 14 to 16 years participated in the study. It was established that the interpersonal relationships of adolescents are closely related to their emotional intelligence. The correlation analysis showed that the level of empathy and emotional intelligence is significantly associated with such types of interpersonal relationships as: sociable, friendly, altruistic, submissive and dependent. The data also emphasize the importance of emotional and social skills in the formation of trusting and stable relationships. It was found that the higher the level of emotional intelligence, the easier and more effective it is for adolescents to build sociable and friendly relationships with others. However, the results of the study showed that a very high level of empathy correlates not only with friendliness, but also with such types of interpersonal relationships as: altruistic, submissive and dependent, which do not always contribute to personal development. Therefore, it is important to work on the development of healthy models of interaction that will help create balanced relationships that take into account the needs of both the individual himself and his social environment.